Contributions of information science in the data science era: Analysis from the Cynefin framework - Sá Ramalho, Rogério Aparecido; Sant'Ana, Ricardo César Gonçalves [UNESP]; Paletta, Francisco Carlos (IGI Global, 2021)
The acceleration of the development of digital technologies and the increase of the capillarity of their effects present new challenges to the praxis related to the treatment and informational flows and those that are object of study of information science. This chapter is based on a theoretical study that analyzes information science contributions in the data science era, analyzing from the Cynefin Framework to the new contemporary informational demands generated by the increasing predominance of data access and use. In order to establish the relationship between the skills expected from the information science professional and its relationship with access to data, the Cynefin Framework was used as a basis to establish a perspective of analyzing the skills involved in each of the phases of the life cycle of the data.